Evaluasi penerapan PSAK 24 tentang imbalan kerja pada PT. Pathemaang Raya Bitung - Takatelide, Gesela; Karamoy, Herman; Gerungai, Natalia Y. Telly (Manajemen Bisnis dan Keuangan Korporat, 2025)
Employee benefits include rewards given to employees or their dependents or beneficiaries, and can be settled through payments (or the provision of goods or services) either directly to employees, their spouses, children, or other dependents, or to third parties such as insurance companies. The aim of this research is to determine the implementation of PSAK 24 on employee benefits at PT Pathemaang Raya Bitung. The data analysis method used in this research is descriptive analysis. Based on the research findings obtained, PT Pathemaang Raya Bitung, in the recognition of employee benefits, has not yet complied with PSAK 24 on employee benefits because it has not recognized bonuses and overtime pay as short-term employee benefits and service awards as other long-term employee benefits.